2019
DOI: 10.3390/md17040208
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan-Stabilized Gold Nanoparticle-Mediated Biofilm Inhibition, Attenuation of Virulence and Motility Properties in Pseudomonas aeruginosa PAO1

Abstract: The emergence of antibiotic resistance in Pseudomonas aeruginosa due to biofilm formation has transformed this opportunistic pathogen into a life-threatening one. Biosynthesized nanoparticles are increasingly being recognized as an effective anti-biofilm strategy to counter P. aeruginosa biofilms. In the present study, gold nanoparticles (AuNPs) were biologically synthesized and stabilized using fucoidan, which is an active compound sourced from brown seaweed. Biosynthesized fucoidan-stabilized AuNPs (F-AuNPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 75 publications
17
34
0
Order By: Relevance
“…They showed the decrease in the biofilm-forming ability of PAO1 using Baicalin-conjugated nanoparticles. Our findings of biofilm inhibition using crystal violet assay agreed with those of Khan et al [44]. They showed that fucoidan-stabilized AuNPs inhibited biofilm formation.…”
Section: Discussionsupporting
confidence: 92%
“…They showed the decrease in the biofilm-forming ability of PAO1 using Baicalin-conjugated nanoparticles. Our findings of biofilm inhibition using crystal violet assay agreed with those of Khan et al [44]. They showed that fucoidan-stabilized AuNPs inhibited biofilm formation.…”
Section: Discussionsupporting
confidence: 92%
“…The antibiofilm efficacy of NQo at sub-MICs was quantified by using crystal violet method [ 25 ]. For this assay, 2 strategies were used.…”
Section: Methodsmentioning
confidence: 99%
“…Qo displays unique properties such as biodegradability and biocompatibility proving to be a simple and cost-effective alternative with many applications such as food safety and biomedicine [ 23 , 24 ]. Qo is known to have antibacterial and antibiofilm properties in Gram-positive bacteria such as Staphylococcus aureus and Gram-negative like Escherichia coli and Salmonella typhimurium [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The detailed characterization of the newly prepared UA-CS NPs was carried out using different instrumentations and the procedures as described earlier [82,83]. The UV-visible-absorption spectroscopy was carried out by scanning over wavelength ranging from 200 to 800 nm using a microtiter plate reader (BioTek, Winooski, VT, USA).…”
Section: Characterization Of Ua-cs Npsmentioning
confidence: 99%
“…The bactericidal properties of UA-CS NPs were determined by microbroth dilution method as described earlier [82]. Briefly, the seed culture of each strain obtained from growing overnight in their respective growth media was being diluted in fresh culture media.…”
Section: Minimum Inhibitory Concentration (Mic) Determination Of Ua-cmentioning
confidence: 99%